Participatory video - International Center for Tropical Agriculture; CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
When a diverse group of women, men, and youth from rural communities learns how to use a video camera, writes their own story, interviews their community figureheads and neighbors and makes their own movie: What is happening behind the filmmaking? “Lights, Camera, Action: Participatory Video to Empower Rural Women and Youth” A collaboration by the International Center for Tropical Agriculture (CIAT), the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the CGIAR Research Program on Integrated Systems for the Humid Tropics (Humidtropics).